Role of Government Institutions in Promoting Sustainable Development in Bangladesh: An Environmental Governance Perspective - Hossain, Imran; Haque, A.K.M. Mahmudul; Ullah, S.M. Akram (UIN Sunan Gunung Djati Bandung, 2023)
This research examines the complex relationship between environmental governance, sustainable development, and the role of government institutions in Bangladesh. The study extensively examines the evolution of environmental governance, focusing on the establishment and functions of key institutions such as the Ministry of Environment and Forests, the Department of Environment, the Department of Forest, the Bangladesh Water Development Board, the Forest Research Institute, etc. Relying solely on secondary sources, the methodology involved a comprehensive review and analysis of scholarly literature, policy documents, and reports to explore the nation's environmental trajectory. The findings underscore the commendable socio-economic progress achieved by Bangladesh compared to pressing environmental challenges. Rising carbon emissions, limited forest coverage, water resource mismanagement, and threats to biodiversity underscore the urgency for balanced and sustainable development. Government institutions, through policy formulation, implementation, research, and conservation efforts, play pivotal roles in addressing these challenges. However, the research highlights the imperative for a paradigm shift, emphasizing the need to integrate environmental considerations into development policies comprehensively. Bridging the gap between economic growth and environmental sustainability requires concerted efforts, policy reforms, and public engagement. This study emphasizes the pivotal role of government institutions, collaborative efforts, and policy reforms in leading the nation towards a more sustainable future.